2013
DOI: 10.2188/jea.je20120053
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Correlation Between Coffee Consumption and Prevalence of Metabolic Syndrome: Baseline Survey of the Japan Multi-Institutional Collaborative Cohort (J-MICC) Study in Tokushima, Japan

Abstract: BackgroundIt is unclear whether consumption of coffee and green tea is associated with metabolic syndrome.MethodsThis cross-sectional study enrolled 554 adults who had participated in the baseline survey of the Japan Multi-Institutional Collaborative Cohort (J-MICC) Study in Tokushima Prefecture, Japan. Consumption of coffee and green tea was assessed using a questionnaire. Metabolic syndrome was diagnosed using the criteria of the National Cholesterol Education Program Adult Treatment Panel III (NCEP ATP III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 43 publications
10
72
0
3
Order By: Relevance
“…Many studies have demonstrated the potential health benefits of daily coffee consumption. Previous epidemiological studies have reported that an increase in daily consumption of coffee was associated with a reduced risk of metabolic syndrome [1][2][3], diabetes [4], and death due to cardiovascular diseases [5]. Similar findings were also true for decaffeinated coffee consumption [6].…”
Section: Introductionsupporting
confidence: 66%
“…Many studies have demonstrated the potential health benefits of daily coffee consumption. Previous epidemiological studies have reported that an increase in daily consumption of coffee was associated with a reduced risk of metabolic syndrome [1][2][3], diabetes [4], and death due to cardiovascular diseases [5]. Similar findings were also true for decaffeinated coffee consumption [6].…”
Section: Introductionsupporting
confidence: 66%
“…One study [37] reported an RR > 1 with 95% CI that did overlap 1.0, while six studies [23][24][25][26]36,39] reported RRs < 1 and 95% CIs not overlapping 1.0. The remaining four studies [27,28,37,39] reported RRs < 1 and 95% CIs overlapping 1.0.…”
Section: Discussionmentioning
confidence: 98%
“…In all, 41 full-text articles were reviewed, with 30 articles excluded because: one was a review; one had duplicate data; and 28 had no reported RRs or 95% CIs for the relationship between coffee intake and MetS. Finally, 11 published articles [23][24][25][26][27][28][35][36][37][38][39], including 13 studies with a total of 159,805 participants, were identified as eligible for the present meta-analysis of the relationship between coffee consumption with MetS risk. Of these, two articles [37,39] included two studies each; four studies were cohort studies with a total of 106,855 participants; eight studies were cross-sectional studies with 52,700 participants; and one was a case-control study with 250 participants.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Some previous studies have suggested the potential association between coffee intake and the risk of metabolic syndrome. [46]…”
Section: Introductionmentioning
confidence: 99%